2019
DOI: 10.1136/bmjdrc-2019-000650
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1α deficiency reduces adiposity, glucose intolerance and hepatic de-novo lipogenesis in diet-induced obese mice

Abstract: ObjectiveWhile extensive research revealed that interleukin (IL)-1β contributes to insulin resistance (IR) development, the role of IL-1α in obesity and IR was scarcely studied. Using control, whole body IL-1α knockout (KO) or myeloid-cell-specific IL-1α-deficient mice, we tested the hypothesis that IL-1α deficiency would protect against high-fat diet (HFD)-induced obesity and its metabolic consequences.Research design and methodsTo induce obesity and IR, control and IL-1α KO mice were given either chow or HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
(62 reference statements)
0
7
1
Order By: Relevance
“…The IL-1 family member IL-1α is a ubiquitous and pivotal pro-inflammatory cytokine ( Cavalli et al, 2021 ). A recent report indicates a possible role of IL-1α in promoting adiposity-induced glucose intolerance and hepatic de-novo lipogenesis ( Almog et al, 2019 ). Here, our results demonstrate that SYT reduces circulatory inflammatory cytokines in HFD-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-1 family member IL-1α is a ubiquitous and pivotal pro-inflammatory cytokine ( Cavalli et al, 2021 ). A recent report indicates a possible role of IL-1α in promoting adiposity-induced glucose intolerance and hepatic de-novo lipogenesis ( Almog et al, 2019 ). Here, our results demonstrate that SYT reduces circulatory inflammatory cytokines in HFD-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 1α (IL-1α) is generally known as an epidermal pro-inflammatory cytokine 48 . It has also been shown that IL-1α knockout mice gained less body fat and did not develop glucose intolerance when fed a high fat diet for 16 weeks 49 . Consistent with prior reports 50 , our data showed that rats fed a high ED diet for 26 weeks have significantly higher levels of IL-1α than low ED fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Its downstream cascade, just as IL-1β signal transduction, includes IL-1R1, IL1RAP, MyD88, and IRAK4 and leads to the launch of proinflammatory NF-κB and MAPK signaling pathways [178]. Mice with this gene knocked out exhibit reduced adiposity [65]. As in mice, a correlation of IL genes with obesity has been shown in humans.…”
Section: Interleukins and Their Receptorsmentioning
confidence: 99%